Step-by-step explanation:
[tex]\dfrac{5}{10}=\dfrac{5:5}{10:5}=\dfrac{1}{2}\\\\\dfrac{5}{10}=0.5[/tex]
x2 + 2x2 + 3x + 6
Factor
Answer:
See Below.
Step-by-step explanation:
I'm going to take the equation to be
y = x3 + 2x2 + 3x + 6
That is, the first term is a typo
make 2 groups. Put brackets around both groups.
group 1: x^3 + 2x^2 Take out the common factor of x^2
group 1: x^2(x + 2)
group 2: 3x + 6 Take out the common factor of x^2
group 2: 3(x + 2)
Now put the two groups together
Cubic = group 1 + group 2
Cubic = x^2 (x + 2) + 3(x + 2)
Now take out the common factor of x + 2
Cubic = (x + 2) (x^2 + 3)
What are the solutions to x2 + 8x + 7 = 0?
A.x= -8 and x = -7
B.x=-7 and x = -1
C.x= 1 and x = 7
D.x= 7 and x = 8
Answer:
B
Step-by-step explanation:
x² + 8x + 7 = 0
x²+x+7x+7=0
x(x+1)+7(x+1)=0
(x+1)(x+7)=0
Either x=-1or x=-7.
If f(x)=-2x-3 find f(4)
Answer:
f(4) = -11
Step-by-step explanation:
Plug in 4 for x: Note that x = 4.
f(x) = -2x - 3
f(4) = -2(4) - 3
Remember to follow PEMDAS. First, solve the multiplication, then subtract:
f(4) = (-2 * 4) - 3
f(4) = (-8) - 3
f(4) = -11
f(4) = -11 is your answer.
~
an app on your phone can estimate your time of arrival when given distance covered. You have travelled 4 1 2 kilometres. The app only accepts improper fractions.
Answer:
?
Step-by-step explanation:
wait is the kilometers number 412 or 41.2?
The mixed fraction 4 1/2 can be converted to the improper fraction 9/2 by multiplying the whole number by the denominator and then adding the numerator.
Explanation:The question is asking you to convert a mixed fraction (4 1/2) into an improper fraction. In your case of 4 1/2, an improper fraction is a fraction where the numerator (the top number) is greater than the denominator (the bottom number). To convert a mixed number into an improper fraction, you multiply the whole number (4) by the denominator of the fractional part (2) and add the numerator of the fractional part (1). This gives you the numerator of the improper fraction.
Here's how you do it: 4*2 = 8, then add 1, which gives you 9. Your improper fraction is thus 9/2.
Learn more about Improper Fractionhttps://brainly.com/question/19318336
#SPJ12
h(x) = 3x - 4
What is h(6)?
ETĀ. 14
e c. 22
SUBMIT
[tex]h(6)=3\cdot6-4=14[/tex]
Answer:
a. 14 is your answer.
Step-by-step explanation:
h(x) = 3x - 4
h(6) = ?
Plug in 6 for x: x = 6
h(6) = 3(6) - 4
Remember to follow PEMDAS. First, multiply, then subtract:
h(6) = (3 * 6) - 4
h(6) = (18) - 4
Simplify:
h(6) = 18 - 4
h(6) = 14
a. 14 is your answer.
~
Solve for x given the equation Vx+9 -4=1. Extraneous or not
Answer:
x=-4/V
Step-by-step explanation:
Add 4 to both sides to cancel out the 4.
So it now the equation is Vx+9=5
Subtract 9 from both sides to cancel out the 9.
Now the equation is Vx=-4
Divide V to both sides to get x alone.
The answer being x=-4/V
For this case we must find the value of "x" of the following equation:
[tex]\sqrt {x + 9} -4 = 1[/tex]
We add 4 to both sides of the equation:
[tex]\sqrt {x + 9} = 4 + 1\\\sqrt {x + 9} = 5[/tex]
We raise both sides of the equation to the square to eliminate the radical:
[tex]x + 9 = 5 ^ 2\\x + 9 = 25[/tex]
We subtract 9 from both sides of the equation:
[tex]x = 25-9\\x = 16[/tex]
Answer:
[tex]x = 16[/tex]
find the value of x if A, B and C are collinear points and B is between A and C. AB= 6x, BC= x-5, AC= 23
Answer:
x=4
Step-by-step explanation:
AB + BC = AC
AB= 6x, BC= x-5, AC= 23
Substituting what we know
6x + x-5 = 23
Combine like terms
7x -5 = 23
Add 5 to each side
7x-5+5 =23+5
7x = 28
Divide each side by 7
7x/7 = 28/7
x=4
Suppose line n has a slope of 5/7 and passes through (4,8). what is the equation for n in point-slope form?
Answer:
[tex]\large\boxed{y-8=\dfrac{5}{7}(x-4)}[/tex]
Step-by-step explanation:
The point-slope form of an equation of a line:
[tex]y-y_1=m(x-x_1)[/tex]
m - slope
We have the slope [tex]m=\dfrac{5}{7}[/tex] and the point [tex](4,\ 8)[/tex].
Substitute:
[tex]y-8=\dfrac{5}{7}(x-4)[/tex]
From the equation, find the axis of symmetry of the parabola. y=-3x^2+3x-13 a. x=1/2 b. x=3 c. x=-1/2 d. x=1
The axis of symmetry of the parabola [tex]y = -3x^2 + 3x - 13[/tex] is x = 1/2.
The axis of symmetry of a parabola in the form [tex]y = ax^2 + bx + c[/tex] is given by the formula x = -b/2a.
In the given equation [tex]y = -3x^2 + 3x - 13[/tex],
we can identify a = -3, b = 3, and c = -13.
The axis of symmetry is then calculated as x = -b/2a:
x = -3/(2*-3) = -3/-6 = 1/2
So, the correct answer is a. x = 1/2.
Regular hexagon FGHIJK shares a common center with square ABCD on a coordinate plane. || . Across which lines can the combined figure reflect onto itself? A. any of the perpendicular bisectors of the sides of the hexagon B. either diagonal of the square C. any of the perpendicular bisectors of the sides of the square D. there are no lines across which this figure can reflect onto itself
Answer:
(C) Any of the perpendicular bisectors of the sides of the square
Step-by-step explanation:
In Regular Hexagon FGHIJK, we have 6 line of reflection across which the hexagon reflects onto itself. Those lines are:
3 perpendicular bisectors of sides i.e. perpendicular bisector of IJ , IH and GH
3 lines passing through vertices i.e. HK, IF and GJ.
While in Square, we have 4 line of reflection across which the square reflects onto itself. Those lines are:
2 perpendicular bisectors of sides AB and BC i.e. HK and perpendicular bisector of CD
2 digonals of square i.e. AC and BD
Also from figure we know that perpendicular bisector of CD and perpendicular bisector of IJ is the same line.
So, for combined figure we have to take common lines from both figures i.e. perpendicular of sides CD or IJ and line HK.
Answer:
Answer C
Step-by-step explanation:
Edmentum
Hook me up with a 5 star and a Thanks
An object is launched from a platform.
Its height (in meters), x seconds after the launch, is modeled by
h(x)=-5(x+1)(x-9)
What is the height of the object at the time of launch?
_________ meters
Please answer as soon as possible please!
Answer:
45 meters
Step-by-step explanation:
If x represents the seconds after the launch, then the time of launch is when x=0 so you just need to solve for h(0)
h(0) = -5(1)(-9)
h(0) = 45
Answer:
45 m
Step-by-step explanation:
At the time of launch, the time x = 0
Substitute x = 0 into h(x)
h(0) = - 5 (0 + 1)(0 - 9) = - 5(1)(- 9) = - 5 × - 9 = 45
how do you calculate the median and mean of X based on the table?
Answer:
The mean is all the #s added up and divided by 5, and median is the number in the middle which is 0.18
Step-by-step explanation:
PLZ vote me for BRAINILEST
the first two steps in determining the solution set of the system of equations y=x^2-6x
+12 and y=2x-4. Which represents the solution(s) of this system of equations?
For this case we have the following system of equations:
[tex]y = x ^ 2-6x + 12\\y = 2x-4[/tex]
Equating the equations:
[tex]x ^ 2-6x + 12 = 2x-4\\x ^ 2-6x-2x + 12 + 4 = 0\\x ^ 2-8x + 16 = 0[/tex]
We look for two numbers that when multiplied, get 16, and when added together, get -8.
These numbers are -4 and -4.
[tex](x-4) (x-4) = 0\\(x-4) ^ 2 = 0[/tex]
So, the solution is[tex]x = 4[/tex]
We look for the value of y:
[tex]y = 2x-4\\y = 2 (4) -4\\y = 8-4\\y = 4[/tex]
Finally, the solution is:[tex](4,4)[/tex]
ANswer:
[tex](4,4)[/tex]
A wall is 15 ft. high and 10 ft. from a house.
Find the length of the shortest ladder which
will just touch the top of the wall and reach a
window 20.35 ft. above the ground.
Answer:
=11.35 ft.
Step-by-step explanation:
The ladder, the flat surface the wall and the height up to the window form a trapezium.
The triangle that constitutes of the trapezium has the ladder as the hypotenuse, the distance between the two walls as base and the perpendicular distance from the base of the ladder to the window as height.
The height=20.35 ft-15 ft= 5.35 ft
Distance between the walls=10 ft
Hypotenuse²= base²+height²
H²=b²+h²
=10²+5.35²
=128.6225
H=√128.6225
=11.35 ft.
Answer:
11.41 ft
Step-by-step explanation:
Same steps as the other guy but, I have the correct answer(especially for Acellus)
solutions to equation x^2 + x - 30 = 12 using zero product property
Answer:
Our solutions are x= -7 , x=6
Step-by-step explanation:
x²+x-30=12
First we calculate the constants:
x²+x-30-12=0
x²+x-42=0
Now split the middle term:
x²+7x-6x-42=0
x(x+7)-6(x+7)=0
(x+7)(x-6)=0
As we know that:
a.b=0
⇒either a=0 or b=0
(x+7)=0 , (x-6)=0
x=0-7 , x=0+6
x= -7 , x=6
So our solutions are x= -7 , x=6....
3 sin^{2} x +cos 2x= (5/4)
answer in radians
Answer:
I believe it's 0.540717
Step-by-step explanation:
3(sin(2))x+(cos(2))(x)=5/4
Simplify: 2.311745x=5/4
Divide: 2.311745x/2.311735=5/4/2.311745
x=0.540717
The height of the parallelogram, h, can be found by dividing the area by the length of the base. If the area of the parallelogram is represented by 4x2 – 2x + 5 and the base is 2x – 6, which represents the height? 2x + 5 + 2x – 7 – 2x – 7 + 2x + 5 –
Answer:
[tex]\frac{4x^{2}-2x+5}{2x-6} =2x + 5 + \frac{35}{2x-6}[/tex]
Step-by-step explanation:
We know that the height of a parallelogram can be found by divind the area by the lenght of the base.
The area is 4x2 – 2x + 5 and the base is 2x – 6. To find the height, we need to divide both polynomials:
[tex]\frac{4x^{2}-2x+5}{2x-6} =2x + 5 + \frac{35}{2x-6}[/tex]
Answer:
[tex]2x+5+\frac{35}{2x-6}[/tex]
Step-by-step explanation:
Given,
The area of the parallelogram, A = [tex]4x^2-2x+5[/tex]
The length of its base, b = [tex]2x-6[/tex]
∵ The height of the parallelogram.
[tex]h=\frac{A}{b}[/tex]
[tex]\implies h=\frac{4x^2-2x+5}{2x-6}[/tex]
[tex]=2x+5+\frac{35}{2x-6}[/tex] ( by long division shown below )
Hence, the height of the given parallelogram is,
[tex]2x+5+\frac{35}{2x-6}[/tex]
Which expression is equivalent to (4 ^5/4 times 4^1/2 divided by 4^1/2)
Answer:
[tex] 2 ^ { \frac { 5 } { 2 } [/tex]
Step-by-step explanation:
We are given the following expression which we are to find its simplest form:
[tex] \frac { 4 ^ { \frac { 5 } { 4 } } \times 4 ^ { \frac { 1 } { 2 } } } { 4 ^ { \frac { 1 } { 2 } } }[/tex]
Cancelling the like terms to get:
[tex] 4 ^ { \frac { 5 } { 4 } } [/tex]
[tex] 2 ^ { 2 .\frac { 5 } { 4 } } = 2 ^ { \frac { 5 } { 2 } } [/tex]
[tex] 2 ^ { \frac { 5 } { 2 } [/tex]
Answer:
B
Step-by-step explanation:
How to solve 3,4 and 6
Answer:
[tex]\large\boxed{3.\ V\approx130.88\ m^3}\\\boxed{4.\ V\approx35.21}\\\boxed{6.\ V\approx1.06\ in^3}[/tex]
Step-by-step explanation:
3.
The formula of a volume of a sphere:
[tex]V=\dfrac{4}{3}\pi R^3[/tex]
R - radius
We have R = 3.15 m. Substitute:
[tex]V=\dfrac{4}{3}\pi(3.15)^3\approx\dfrac{4}{3}\pi(31.26)\approx\dfrac{4}{3}(3.14)(31.26)\approx130.88\ m^3[/tex]
4.
The formula of a volume of a cone:
[tex]V=\dfrac{1}{3}\pi r^2H[/tex]
r - radius
H - height
We have 2r = 11.6 → r = 5.8 and H = x. Substitute:
[tex]V=\dfrac{1}{3}\pi(5.8)^2(x)=\dfrac{1}{3}\pi(33.64)x\approx\dfrac{1}{3}(3.14)(33.64)x\approx35.21[/tex]
6.
The formula of a volume of a cube:
[tex]V=s^3[/tex]
s - edge
We have s = 1.02 in. Substitute:
[tex]V=(1.02)^3\approx1.06\ in^3[/tex]
You put $280 in a one-year CD that will earn 4.5% a year, calculated semiannually. How much simple interest will you earn?
Answer:
25.77 dollars
Step-by-step explanation:
280 × .045 = y
y + 280 = z
z × .045 = c
z + c = d
d - c = the answer. $25.77
All of the following are equivalent except___. 7x^3,4x+3x,(4+3)x,7x
Answer:
The one that is not equivalent is 7x^3
Step-by-step explanation:
7x^3= 7 * x*x*x
4x+3x = 7x = 7*x
(4+3)x = (7)x = 7*x
7x= 7*x
Answer:
7x^3
Step-by-step explanation:
All of the following are equivalent except 7x^3.
7x^3 = 7x^3
4x+3x = 7x
(4+3)x = 7x
7x = 7x
QP contains the points Q(-6,10) and P(-12,-2). Find the slope of a line perpendicular to QP
Answer: -2
Step-by-step explanation: Find the slope of between the two points. P is the bottom point and Q is the top point. Both x and y numbers increase, meaning that the slope is positive. The x numbers increase by 6, and the y numbers increase by 12. This means that the rise is 12, and the run is 6. The slope is 12/6 but can be simplified to 2/1. The perpendicular slope is -1/2 because the perpendicular slope of a line is opposite reciprocal. This means to make the number negative and to flip it.
Answer:
-1/2
Step-by-step explanation:
So we are asked to find the slope of a line perpendicular to the line going through Q(-6,10) and P(-12,-2).
To do this we first need to find the slope of the line going through Q(-6,10) and P(-12,-2).
We can use the slope formula for a line given two points on that line which is (y2-y1)/(x2-x1).
I like to do something I consider easier to remember and is the same thing
It is:
A) line up the points
B) subtract vertically
C) put 2nd difference over first difference
D) done unless it needs reducing
So that is exactly what I'm going to do here:
(-6, 10)
-(-12,-2)
------------
6 12
So the slope is 12/6 or 2.
Now you might prefer to write 2 as a fraction now, because I'm about to tell you to find the slope of a line that is perpendicular, you just need to take the opposite reciprocal.
Opposite means to change the sign. I'm referring to negative or positive sign.
Reciprocal means to flip the number.
Let's put 2 through that process.
Opposite of 2: -2
Reciprocal of the opposite: -1/2
I got that reciprocal there by realizing -2 is just -2/1.
Anyways the slope of a line that is perpendicular to the one that goes through P and Q is -1/2 or -0.5.
1,547.489 which digit is in the ten place
1,547.489
4 - Bold and underline one above is in the ten place.
Answer:
1,547.489
Step-by-step explanation:
Note that there is a decimal point in between 7 & 4, and the numbers to the left are whole numbers, while the numbers to the right is part of the decimal.
From the decimal point, count to the left two place value (to find the tens place):
1,547
1,547
4 is your digit in the ten's place, & is your answer.
~
If you are given the graph of h(x)=log(6)x, how could you graph m(x)=log(6)(x+3)? Translate each point of the graph of h(x) 3 units up. Translate each point of the graph of h(x) 3 units down. Translate each point of the graph of h(x) 3 units right. Translate each point of the graph of h(x) 3 units left.
Answer:
Last option: Translate each point of the graph of h(x) 3 units left.
Step-by-step explanation:
There are some transformations for a function f(x). The following is one of these transformations:
If [tex]f(x+k)[/tex], then the function is shifted "k" units to the left.
Given the function [tex]h(x)=log_6(x)[/tex] and the function [tex]m(x)=log_6(x+3)[/tex], you can notice that the function m(x) is the function h(x) but shifted left 3 units.
Therefore, you could graph the function m(x) by translating each point of the graph of the function h(x) 3 units left.
This matches with the last option.
Answer:
Last option (D) Translate each point of the graph of h(x) 3 units left.
Simplify (Y^2+7y+6)/(6y^2-6)
Answer:
[tex]\frac{y + 6}{6(y - 1)} [/tex]
Step-by-step explanation:
The given expression is
[tex] \frac{ {y}^{2} + 7y + 6}{6 {y}^{2} - 6} [/tex]
The numerator is a quadratic trinomial and the denominator is different of two squares when 6 is factored.
We factor both the numerator and the denominator to obtain;
[tex] \frac{ (y + 6)(y + 1) }{6(y - 1)(y + 1)} [/tex]
Cancel out the common factors to get:
[tex] \frac{y + 6}{6(y - 1)} [/tex]
This is the simplest form since, we cannot simplify this further.
For this case we must simplify the following expression:
[tex]\frac {y ^ 2 + 7y + 6} {6y ^ 2-6}[/tex]
We factor the numerator, looking for two numbers that when multiplied by 6 and when added together give 7. These numbers are +6 and +1.
Then, rewriting the expression:
[tex]\frac {(y + 6) (y + 1)} {6 (y ^ 2-1)} =[/tex]
We rewrite the denominator:
[tex]\frac {(y + 6) (y + 1)} {6 (y + 1) (y-1)} =[/tex]
We simplify similar terms:
[tex]\frac {(y + 6)} {6 (y-1)}[/tex]
Answer:
[tex]\frac {(y + 6)} {6 (y-1)}[/tex]
8 lbs of cashew nuts cost $32. What is the cost of one pound?
Answer:
$4 per pound
Step-by-step explanation:
To find how much one pound of cashew nuts cost you have to use money over unit.
So money/unit, in this problem the money is 32 and the unit is 8.
So 32/8, now you divide 32 by 8 to get the price for one pound.
32 divided by 8 is 4
So $4 per pound
Answer:
The total cost of one pound is $4.
Step-by-step explanation:
[tex]\Large\textnormal{First, you divide the numbers from left to right to find the answer.}[/tex]
[tex]\displaystyle 32\div8=4[/tex]
[tex]\displaystyle \frac{8}{8}=1[/tex]
[tex]32\div4=8[/tex]
[tex]\displaystyle \frac{32}{8}=4\times1=4[/tex]
[tex]\Large \boxed{4}[/tex], is the correct answer.
I hope this helps you and have a wonderful day!
A teacher needs to choose seven students to hand out papers. The total number of ways he may choose the students can be found using a combination
Answer:
True
Step-by-step explanation:
Apex
Which statements are true regarding the prism? Check
all that apply.
The prism has no vertices.
The prism has 9 edges.
The bases of the prism are triangles.
The bases of the prism are rectangles.
The prism has 5 faces.
O
Answer:
1. The base is a triangle.
Step-by-step explanation: This one seems like it's the only corret one, You might have to wait and see the other answers roll in.
Answer:
2,3&5
Step-by-step explanation:
got it right on edg 2020
A small bat weighs about 2/5 of an ounce. A small hummingbird weighs about 14/25 of an ounce. Explain how to find the difference in the weights of these animals
Answer:
The difference is about [tex]\frac{4}{25}[/tex] of an ounce
Step-by-step explanation:
we know that
A small bat weighs about 2/5 of an ounce
A small hummingbird weighs about 14/25 of an ounce
step 1
Multiply 2/5 by 5/5
Remember that
5/5 is 1
so
[tex](\frac{2}{5})(\frac{5}{5})=\frac{10}{25}[/tex]
step 2
To find the difference in the weights of these animals, subtract the weight of the small bat from the weight of the small hummingbird
[tex](\frac{14}{25})-(\frac{10}{25})[/tex]
Remember that
When subtract fractions with the same denominators, subtract the top numbers and put the answer over the same denominator
so
[tex](\frac{14}{25})-(\frac{10}{25})=\frac{4}{25}[/tex]
therefore
The difference is about [tex]\frac{4}{25}[/tex] of an ounce
What is the y-value of the vertex of the function f(x)=-(x-3)(x+11)
so, this is a quadratic equation, meaning two solutions, and we have a factored form of it, meaning you can get the solutions by simply zeroing out the f(x).
[tex]\bf \stackrel{f(x)}{0}=-(x-3)(x+11)\implies 0=(x-3)(x+11)\implies x= \begin{cases} 3\\ -11 \end{cases} \\\\\\ \boxed{-11}\stackrel{\textit{\large 7 units}}{\rule[0.35em]{10em}{0.25pt}}-4\stackrel{\textit{\large 7 units}}{\rule[0.35em]{10em}{0.25pt}}\boxed{3}[/tex]
so the zeros/solutions are at x = 3 and x = -11, now, bearing in mind the vertex will be half-way between those two, checking the number line, that midpoint will be at x = -4, so the vertex is right there, well, what's f(x) when x = -4?
[tex]\bf f(-4)=-(-4-3)(-4+11)\implies f(-4)=7(7)\implies f(-4)=49 \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ ~\hfill \stackrel{vertex}{(-4~~,~~49)}~\hfill[/tex]